The Transforming Power of Literacy - Bush, Barbara (Maine Policy Review, 2009)
In the Margaret Chase Smith Essay, former First Lady Barbara Bush discusses the importance of family literacy for preschool and school-aged children and their families. Children enrolled in these programs show significant progress in reading levels and are less likely to drop out of school. Adult participants have greatly improved their reading skills, are more involved in their children’s education, and are better prepared to be good employees.
Keywords: Maine; family literacy